Assessing Window Design for Healing Environment in Selected Hospitals - Amin, Said Ul; Ullah, Ubaid; Din, Misbahud (Annals of Human and Social Sciences, 2024)
This study examine the important characteristics of window design in selected hospital wards and how they impact patients' perception of health, with a particular emphasis on improving the healing environment. The architecture and environment of a hospital significantly impact patients' recovery. Hospital's layout and facilities can either expedite or impede the healing process, depending on their configuration. Windows have been identified as a crucial element of hospital architecture that can influence the patient recovery, along with other aspects of hospital design. This research employs a holistic methodology by integrating objective assessments of window characteristics with subjective evaluations of patient preferences. Five hospitals were deliberately chosen for examination, and the window qualities of one medical ward from each hospital were carefully examined via objective observation and subjective responses from the patients. The results of this study emphasizes the importance of holistic design strategies that harmoniously integrate physical attributes with psychological experiences.